2021
DOI: 10.2337/db21-1024-p
|View full text |Cite
|
Sign up to set email alerts
|

1024-P: Association, Prevalence, and Occurrence of Depression and Anxiety in Indian T2DM Patients

Abstract: Background: Depression is found to be common among patients with diabetes and it is associated with poor outcomes in disease control. Mani objective of the study was to study the prevalence and occurrence of depression and anxiety in patients of type 2 diabetes mellitus (T2DM). Materials:115 adults with T2DM without prior diagnosis of depression and 115 matched controls were evaluated. Sociodemographic and relevant clinical variables were collected. They were evaluated for depression and anxiety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Depression is also related to poor health behaviors such as sedentary lifestyle, poor adherence to drugs, diet, and exercise regime which further enhance the risk of diabetes. Our findings are in accordance with an earlier study by Kumar et al [9] which reported the prevalence of depression in T2DM to be 33%. Many case-control studies which compared the prevalence of depression [19][20][21] reported a significantly high rate of depression among the diabetic patients than the nondiabetic controls.…”
Section: Prevalence and Severity Of Depressionsupporting
confidence: 94%
See 3 more Smart Citations
“…Depression is also related to poor health behaviors such as sedentary lifestyle, poor adherence to drugs, diet, and exercise regime which further enhance the risk of diabetes. Our findings are in accordance with an earlier study by Kumar et al [9] which reported the prevalence of depression in T2DM to be 33%. Many case-control studies which compared the prevalence of depression [19][20][21] reported a significantly high rate of depression among the diabetic patients than the nondiabetic controls.…”
Section: Prevalence and Severity Of Depressionsupporting
confidence: 94%
“…In a previous study, Kumar et al . [9] concluded that the prevalence rate of depression was higher in ages between 41 and 60 years (18.8% vs. 7.6%, respectively) in the diabetic and healthy control groups. A study by Raval et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations